Bit error rate measurement on WCDMA system in multipath channel - Abdul Rahman, Tharek (IEEE, 2004)
This paper discusses the principle of WCDMA that supports the high data rate transmission. The basic transmitter and receiver characteristics of WCDMA system that conforming to 3GPP specification is also presented in this paper. The bit error rate (BER) of a WCDMA system at downlink direction for different channel conditions is investigated. The multipath fading channel used for the simulation is based on the IMT-2000 standard specification.